2012
DOI: 10.1016/j.jcmg.2012.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Mediated Vascular Gene Transfection by Cavitation of Endothelial-Targeted Cationic Microbubbles

Abstract: OBJECTIVES Ultrasound-mediated gene delivery can be amplified by acoustic disruption of microbubble carriers that undergo cavitation. We hypothesized that endothelial targeting of microbubbles bearing cDNA is feasible and, through optimizing proximity to the vessel wall, increases the efficacy of gene transfection. BACKGROUND Contrast ultrasound-mediated gene delivery is a promising approach for site-specific gene therapy, although there are concerns with the reproducibility of this technique and the safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 21 publications
(31 reference statements)
3
70
1
Order By: Relevance
“…We reported that the transfection efficiencies that can be reached with mRNA sonoporation are significantly lower than when mRNA is electroporated into DCs, however it should be noted that the importance of mRNA sonoporation as a transfection technique lies within its possible in vivo applicability [42,43]. Commercially available microbubble contrast agents were shown to migrate to the tumor-draining lymph nodes upon intradermal injection around the tumor of breast cancer patients [15].…”
Section: Discussionmentioning
confidence: 97%
“…We reported that the transfection efficiencies that can be reached with mRNA sonoporation are significantly lower than when mRNA is electroporated into DCs, however it should be noted that the importance of mRNA sonoporation as a transfection technique lies within its possible in vivo applicability [42,43]. Commercially available microbubble contrast agents were shown to migrate to the tumor-draining lymph nodes upon intradermal injection around the tumor of breast cancer patients [15].…”
Section: Discussionmentioning
confidence: 97%
“…In another study ovarian cancer cells were transfected with wild-type p53 tumour suppressor gene using luteinising hormone-releasing hormone analogue (LHRHa)-tUCA to induce apoptosis (1 MHz, 0.5 W/cm 2 , 30 s treatment) [185]. Two studies [186,187] showed that tUCAs loaded with luciferase plasmid can transfect vasculature in vivo. Xie et al [186] used P-selectin tUCAs in a hind limb ischaemia skeletal muscle model (see Figure 3E; 1.6 MHz, 0.6-1.8 MPa, power Doppler, pulsing interval 5 s, PRF 2.5 kHz for 10 min), whereas Tlaxca et al [187] [190].…”
Section: Enhanced Drug Deliverymentioning
confidence: 99%
“…Two studies [186,187] showed that tUCAs loaded with luciferase plasmid can transfect vasculature in vivo. Xie et al [186] used P-selectin tUCAs in a hind limb ischaemia skeletal muscle model (see Figure 3E; 1.6 MHz, 0.6-1.8 MPa, power Doppler, pulsing interval 5 s, PRF 2.5 kHz for 10 min), whereas Tlaxca et al [187] [190]. In vivo, the tUCAs were administered intraperitoneally allowing the tUCAs to adhere to the ovarian cancer cells.…”
Section: Enhanced Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations